Pelatihan Manajemen Emosi Sebagai Program Pemulihan Depresi pada Remaja Korban Gempa Bumi - Zarina Akbar; Tina Afiatin (JIP (Jurnal Intervensi Psikologi), 2009)
Yogyakarta's earthquake survivors oÃ±en show depression symptoms. This study is aimed to recognize the effectiveness of emotional management training on mitigating depressed adolescents of Yogyakarta's earthquake survivors. Twenty participants enrolled within, which are categorized into experiment and control group. The participant's characteristics were: second year in junior high school, survivors of Yogyakarta's earthquake, age ranging from 13 to 15. The hypotheses sugaest that emotional management training is effective to decrease depression among adolescents of Yogyakarta's earthquake victim. Beck Depression Inventory was conducted before, after, and at the follow-up to measure depression. Result shows that emotional management training is effective in decreasing depression among adolescents of Yogyakarta's earthquake survivors. Qualitative analysis found that individuals which shows higher hate of declining depression score have different emotion management process compared to the lower. It suggested to next research to focus continously to improve the effectiveness of the training.Keywords: Yogyakarta's earthquake survivors, Emotion Management Training, Depression